Mortars with incorporation of phase change materials for thermal rehabilitation - Cunha, Sandra Raquel Leite (2017)
The thermal rehabilitation is an opportunity to reach higher levels of energetic performance, reducing the high energetic dependence of the countries. Rehabilitation operations based in the utilization of materials with the capability to store and release energy contribute to obtain more energy efficient buildings. Combining the use of smart materials with temperature control capability and renewable energy sources, it is possible to increase the thermal comfort inside the buildings. The main purpose of this study was the physical, mechanical, and thermal characterization of mortars based in specific binders for rehabilitation with incorporation of phase change materials (PCM). Mortars without and with incorporation of PCM were studied. It was observed that the incorporation of PCM in mortars caused differences in the physical and mechanical properties and improved their thermal behavior, reducing the extreme temperatures and decreasing the heating and cooling needs.